A Sensitive Voltammetric Approach Employing a Bare Boron-Doped Diamond Electrode as a Sensor for the Determination of Hydroxocobalamin - Janíková, Lenka; Šelešovská, Renáta; Stýblová, Iveta; Chýlková, Jaromíra (MDPI AG (Multidisciplinary Digital Publishing Institute), 2023)
The voltammetric behavior of hydroxocobalamin (OH-CBL) was firstly studied by employing a bare boron-doped diamond electrode as a working electrode. It was found that OH-CBL provided four anodic signals on BDDE in acidic supporting electrolytes and one cathodic signal. The anodic peak situated at +412 mV (vs. Ag|AgCl|KCl (sat.) recorded in 0.1 mol/L H2SO4) was found to be suitable for analytical purposes due to its position and shape. A novel voltammetric approach based on differential pulse voltammetry was developed and it was found as a sensitive analytical tool, with low limit of detection (LD = 13.2 nmol/L), applicable in analysis of vitamin preparations.
Vývoj citlivé voltametrické metody pro stanovení hydroxokobalaminu s yvužitím bórem dopované diamantové elektrody jako senszoru
Keywords: hydroxocobalamin; vitamin B12; boron-doped diamond electrode; voltammetry; vitamin analysis; hydroxokobalamin; vitamin B12; bórem dopovaná diamantová elektroda; analýza vitaminů